POTENTIAL FOR MARINE ECOTOURISM DEVELOPMENT AT SUNUA BEACH PARIAMAN CITY WEST SUMATERA PROVINCE - Ikhsan, Miftahul; Samiaji, Joko; Nasution, Syafruddin (Asian Journal of Aquatic Sciences, 2024)
ABSTRACT Produces economic benefits for people in the area and the surrounding area. The tourism potential of Sunua Beach is not yet known from scientific studies. The lack of information regarding this research location means that many foreign tourists need to learn about this tourist location. The research was conducted in February-March 2024 at Sunua Beach, Pariaman City, West Sumatra Province. The study aims to identify the potential and objects that need to be developed at Sunua Beach as a marine ecotourism area, to determine public perceptions, and to formulate a strategy for developing marine ecotourism to support sustainable tourism. The method used in research is a survey method. The placement of station points was carried out using the purposive sampling method. The water quality measurements were observed by temperature, brightness, salinity, pH, current speed, water depth, and beach slope. The selection of respondents each consisted of 15 tourists, 15 local communities, 10 business actors, and 10 policymakers. Based on the tourism suitability index, Sunua Beach is included in the S1 category (very suitable) with tourist suitability index values of 83.97%, 86.53%, and 83.97%, respectively, on SWOT analysis through observation and identification of various factors in the field, the results obtained a member of strengths, weaknesses, opportunities and threats at Sunua Beach. The results of the analysis will